Surréalisme et modernisme - Losada Goya, José Manuel (Thélème. Revista Complutense de Estudios Franceses, 2009)
El debate en torno al modernismo y las vanguardias continúa. Retomando algunas definiciones de un estudio previo, este artículo aborda diversas cuestiones sobre el problema de la temporalidad, las relaciones entre estos movimientos con el esoterismo y las dificultades que obstaculizan el paso de los proyectos surrealistas a sus realizaciones literarias. - The discussion about Modernism and the Avant-Garde movements goes on. According to some definitions stated in a previous study, this article tackles different questions concerning the relationship between these two movements and chronology, esoteric issues, and the difficulties the Surrealism is faced with when it comes to realise its main projects.